Evaluating effect of cover crops on runoff, soil loss and soil nutrients in an Indian arid region. Issue 14 (6th August 2021) - Machiwal, Deepesh; Kumar, Sushil; Islam, Adlul; Kumar, Sanjay; Jat, Sita Ram; Vaishnav, Meera; Dayal, Devi
ABSTRACT: Estimates of the soil and nutrient losses are essential for design and planning of soil conservation measures in Indian arid region. This study aims at estimating rainfall-runoff, soil and nutrient losses from different cover crops, and to identify the best cover for checking soil loss. The study is conducted for 2013–2015 in research farm of the Central Arid Zone Research Institute, Regional Station, Bhuj, Gujarat, India. Ten treatments comprising four sole-crop, that is, sorghum ( Sorghum bicolor ), pearl millet ( Pennisetum glaucum ), green gram ( Vigna radiata ), and cluster bean ( Cyamopsis tetragonoloba ) and four cereal-legume intercropping with two controls (cultivated and unplowed fallows) are undertaken in randomized block design with three replications. Multi-slot divisors are fabricated and installed. Analysis of variance (ANOVA) is performed, and their interrelationships are explored. The highest soil loss is recorded from cultivated fallow (108.03 ± 49.95 kg.ha −1 .yr −1 ) and unplowed fallow (78.95 ± 28.42 kg.ha −1 .yr −1 ). Green gram is found effective in controlling soil loss as sole-crop (event-wise soil loss 0.54–33.94 kg.ha −1 ) as well as intercropping with sorghum (event-wise soil loss 0.60–23.37 kg.ha −1 ) and pearl millet (event-wise soil loss 2.45–31.11 kg ha −1 ). ANOVA revealed significance ( p < .05) of runoff-generating rainfall, crop cover, and their sole- and intercropping practices. Values of coefficient of determination (R 2 ) indicated highly correlated (R 2 ≥ 0.75) relationships of rainfall-runoff for all treatments, rainfall-soil loss for sole cereals and cultivated fallow, and runoff-soil loss for pearl millet and intercropping with green gram. This study concludes that cereal-legume intercropping diminishes the adverse impact of raindrops on soil erosion and crop production.